The bumble bees (Hymenoptera: Apidae: Bombus) of Arkansas, fifty years later - Tripodi, Amber D.; Szalanski, Allen L. (Journal of Melittology, 2015)
Many species of bumble bees (Hymenoptera: Apidae: Bombus Latreille) are declining throughout their ranges in North America, yet detecting population trends can be difficult when historical survey data are lacking.  In the present study, contemporary data is compared to a 1965 survey to detect changes in bumble bee distributions throughout Arkansas.  Using county-level records as a point of comparison to look for changes in state-wide occurrence among species over time, we find that state-level changes reflect national trends.  Contemporary records of Bombus bimaculatus Cresson and B. impatiens Cresson have more than tripled, while records for B. pensylvanicus (De Geer) show a decline to 61% of historical levels.  Although B. fervidus (Fabricius) has been reported infrequently in the state, misidentifications may have led to an overestimation of the state’s species richness.  In addition to an updated assessment of the bumble bees of Arkansas, we also provide new, localized information on the seasonal phenology and plant preferences of each species that can be used to guide conservation efforts.